Risk and Resilience for Family Livestock Producers in the Protected Area of Esteros de Farrapos National Park, Uruguay - Gazzano, Inés; Altieri, Miguel; Achkar Borrás, Marcel; Burgueño, Juan (Agrociencia Uruguay, 2016)
The risk of family farmers in the Protected Area Esteros de Farrapos (APEF) increases with synergy between flooding and reduced grazing areas outside the estuary. This study analyzed the extent of the frequency of flooding by determining the height of the water surface of the río Uruguay in a period of eight years and the number of days when the water level exceeded the thresholds handled by producers. The paper analyzes the ways livestock producers internalize the risk. The risk was analyzed with the holistic risk index (Barrera et al., 2007) that combines threat, responsiveness and vulnerability. The water height thresholds were determined by in-depth interviews. The water exceeded the threshold of 3 masl, therefore cattle have to be out of the estuary, during 334 days out of a total of 2914 presenting a seasonal distribution with major frequency in the following order: spring-summer-winter-autumn. Four producers have low risk due to high responsiveness; 18 present medium risk divided in: high vulnerability and lower vulnerability and increased responsiveness; and three producers are at a high risk due to high threat and vulnerability and lower responsiveness. The relationship threat-responsiveness was inversely proportional and significant. Responsiveness linked with agro-ecological principles and criteria helps orienting strategies between producers and managing of the area.